Global low order spectral model designed for climate sensitivity studies - Hanna, Adel F., author; Stevens, Duane E., author (Colorado State University. Libraries, 1984)
A two-level, global, spectral model using pressure as a vertical coordinate is developed. The system of equations describing the model is nonlinear and quasi-geostrophic (linear balance) (Lorenz, 1960). A moisture budget is calculated in the lower layer only with moist convective adjustment between the two layers. The mechanical forcing of topography is introduced as a lower boundary vertical velocity. Solar forcing is specified assuming a daily mean zenith angle. On land and sea ice surf aces a steady state thermal energy equation is solved to calculate the surface temperature. Over the oceans the sea surface temperatures are prescribed from the climatological average of January. The model is integrated to simulate the January climate.
March 1984.
Keywords: Atmospheric circulation; Atmospheric diffusion; Climatic changes